THE ROLE OF FORENSIC LINGUISTICS IN RESOLVING LINGUISTIC DISPUTES IN UZBEKISTAN - Ashurov, Bobir (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2024)
Forensic linguistics, a multidisciplinary field that applies linguistic analysis to legal and professional contexts, plays a critical role in legal proceedings and investigations. This study explores its applications in Uzbekistan, where the intersection of linguistics and law is particularly significant due to the country’s linguistic diversity and socio-cultural dynamics. The article examines cases involving insults (haqorat), defamation (tuhmat), and other contentious languages, analyzing speech and text’s semantic, syntactic, and pragmatic features. It highlights the methodological challenges of regional dialects, cultural idioms, and hierarchical social structures. Additionally, the study addresses the broader applications of forensic linguistics, including analyzing extremist materials, authorship disputes, and evaluating legal documents. Recommendations include establishing linguistic databases, training programs for forensic linguists, and policy reforms to enhance linguistic expertise in legal contexts. The findings underscore the vital role of forensic linguistics in ensuring fairness, accountability, and justice in Uzbekistan’s legal system, emphasizing the importance and impact of the field.